The maintenance on salinity effect on reinforcement concrete structure at coastal area / Harmidzy Muhamad Har - Muhamad Har, Harmidzy (Faculty of Architecture, Planning and Surveying, 2014)
Development at coastal area has its own demand either for residential, recreation or tourism purposes. Thus, a lot of new building construction can be seen at along coastline in order to fulfill the demand. Building that constructed along coastline likely can be effected by salinity since it built nearby sea especially building that has physical contact with sea water, such as chalets built above the sea water. Salinity can be found in sea water where it refers to concentration of salt element that contains in sea water. The aim of this dissertation is to establish factors that need to be considered by the maintenance team on the salinity effect on reinforcement concrete building structure at coastal area.Three chalet development located at coastline and built above sea water has been chosen for the case study. The first objective of this dissertation is to find out the properties of saline water that contribute to deterioration of reinforcement concrete structure. The second objective is to find the common defect of reinforced concrete structure on building at coastal areas. For the third objective is to examine the consequences of the salinity effect if no remedy’s action taken. The method of data collection is through interview with maintenance department representative and condition survey on the selected case studies. For condition survey, it carries out and focus on defect that occur in reinforced concrete structure such as column, beam and slab. Then after all data, finding analyze, conclusion and recommendation provided according to the objective of this dissertation. The result of this dissertation show all maintenance representative lack of information about effect of salinity on reinforcement concrete. On the other hand, condition survey result show defect cause by salinity are not treated properly by the maintenance team. Thus the maintenance team should be equip with information about the effect of salinity through workshop or other learning process. This is important to make sure building around coastal area are maintained properly from defect cause by salinity.